Analisis Kemampuan Representasi Matematis Siswa Ditinjau dari Kemampuan Awal Matematis Siswa pada Materi Himpunan - Gunawan Gunawan; Citra Utami; Rika Wahyuni (Departement of Mathematics Education, 2024)
This study aims to describe students' mathematical representation abilities in terms of students' initial mathematical abilities in solving problems on set material. This type of research is a qualitative description. The subjects in this study were class VII D at SMPN 04 Singkawang. The instrument used in this research is a mathematical representation ability test. As well as interviews to support the test results in this study. Based on the results of the data analysis, it can be seen that 1) Students who have initial mathematical abilities in the upper group have moderate level of mathematical representation skills with moderate level of verbal representation skills, moderate level of symbol representation skills and moderate level of visual representation abilities. 2) Students who have early middle group mathematical ability have moderate level of mathematical representation ability with moderate level of verbal representation ability, medium level of symbol representation ability and medium level of visual representation ability. 3) Students who have early mathematical abilities in the lower group have moderate level of mathematical representation skills with moderate level of verbal representation skills, moderate level of symbol representation skills and moderate level of visual representation abilities.